Tuning spectral properties of phenothiazine based donor-pi-acceptor dyes for efficient dye-sensitized solar cells - Marszalek, Magdalena; Nagane, Satyawan; Ichake, Amol; Humphry-Baker, Robin; Paul, Vincent; Zakeeruddin, Shaik M.; Graetzel, Michael (Journal of Materials Chemistry, 2012)
Two novel metal-free organic donor-pi-acceptor dyes were synthesized using electron-rich 10-butyl-(2-methylthio)-10H-phenothiazine as a donor and cyanoacrylic acid as an acceptor. The spectral response of the dye was tuned by introducing a vinylene thiophene pi-bridge. Obtained optical and electrochemical properties of the dyes seemed to be promising in terms of employing them as light harvesters in dye-sensitized solar cells (DSCs). The efficiencies of the devices under standard AM 1.5G (100 mW cm(-2)) conditions reached 7.3% with volatile electrolyte. The differences in the photovoltaic parameters of these DSCs were explained by comparing the results of electrochemical impedance spectroscopy (EIS) measurements and transient photovoltage and photocurrent decay experiments.